2023
DOI: 10.1164/rccm.202208-1570oc
|View full text |Cite
|
Sign up to set email alerts
|

A Pathology-based Case Series of Influenza- and COVID-19–associated Pulmonary Aspergillosis: The Proof Is in the Tissue

Abstract: Rationale Invasive pulmonary aspergillosis has emerged as a frequent coinfection in severe coronavirus disease (COVID-19), similarly to influenza, yet the clinical invasiveness is more debated. Objectives We investigated the invasive nature of pulmonary aspergillosis in histology specimens of influenza and COVID-19 ICU fatalities in a tertiary care center. Methods In this monocentric, descriptive, retrospective case series, we included adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…The diagnostic criteria for these co-infections combine clinical, radiological, mycological, and histological criteria [ 4 ]. A recent autopsy study on patients infected with influenza and COVID-19 confirmed the invasive nature of the infection and the similarity of histological lesions observed in both IAPA and CAPA cases [ 5 ]. A multicenter French study conducted during the first wave revealed that 15% of critically ill patients with COVID-19 requiring invasive mechanical ventilation (IMV) fulfilled the diagnostic criteria for CAPA, which was also associated with poor outcomes [ 1 ].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The diagnostic criteria for these co-infections combine clinical, radiological, mycological, and histological criteria [ 4 ]. A recent autopsy study on patients infected with influenza and COVID-19 confirmed the invasive nature of the infection and the similarity of histological lesions observed in both IAPA and CAPA cases [ 5 ]. A multicenter French study conducted during the first wave revealed that 15% of critically ill patients with COVID-19 requiring invasive mechanical ventilation (IMV) fulfilled the diagnostic criteria for CAPA, which was also associated with poor outcomes [ 1 ].…”
Section: Introductionmentioning
confidence: 81%
“…Thus, the prognostic relevance of CAPA per se could be questioned: it might be considered a simple severity indicator rather than a truly invasive super-infection. A recent pathology-based studies has highlighted the invasive nature of CAPA [ 5 ], thereby supporting systematic CAPA screening of intubated patients and specific antifungal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…ICU physicians do not always consider the possibility of IPA in patients without classic host risk factors. 30 However, autopsy studies show that IPA remains one of the most common missed diagnoses among patients admitted to a medical ICU 31 32 33 34 : in one autopsy study on 893 ICU patients, only 40% of the IA cases diagnosed at autopsy had been recognized ante-mortem. 34 Although classical host risk factors might not always be present, most patients do have underlying comorbidities: in a prospective cohort study of 297 ICU patients with IA, only 5% had no underlying disease.…”
Section: Epidemiologymentioning
confidence: 99%
“…Autopsy studies show that diagnosis of IPA is still often missed, demonstrating the persisting limitations of our diagnostic tests and approaches. 3 4 5 6 Even more challenging is the diagnosis of fungal coinfections. Coinfections with Aspergillus and Mucorales are more common than previously thought.…”
Section: Tablementioning
confidence: 99%